2008
DOI: 10.2337/dc08-s247
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidases, Reactive Oxygen Species, and Hypertension

Abstract: Reactive oxygen species (ROS) influence many physiological processes including host defense, hormone biosynthesis, fertilization, and cellular signaling. Increased ROS production (termed "oxidative stress") has been implicated in various pathologies, including hypertension, atherosclerosis, diabetes, and chronic kidney disease. A major source for vascular and renal ROS is a family of nonphagocytic NAD(P)H oxidases, including the prototypic Nox2 homolog-based NAD(P)H oxidase, as well as other NAD(P)H oxidases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
436
2
23

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 634 publications
(474 citation statements)
references
References 161 publications
13
436
2
23
Order By: Relevance
“…The major sources of ROS at vascular level are NADPH oxidase and mitochondria 46, 47, 48. Our data show for the first time that BCAA produce functional effects on the vascular wall.…”
Section: Discussionmentioning
confidence: 58%
“…The major sources of ROS at vascular level are NADPH oxidase and mitochondria 46, 47, 48. Our data show for the first time that BCAA produce functional effects on the vascular wall.…”
Section: Discussionmentioning
confidence: 58%
“…Our current study shows for the first time that canola oil intake with salt reduces NADPH oxidase subunits and SOD isoforms in the aorta of SHRSP rats after 25 days of feeding. Evidence has shown that ·O 2 ˉ generated from NAPDP oxidase is increased in hypertension [16]. In addition, Kitiyakara et al found that salt intake in Sprague-Dawley rats lead to an increase in ·O 2 ˉ production [23].…”
Section: Discussionmentioning
confidence: 99%
“…In hypertensive patients, vascular smooth muscle cells (VSMCs) from resistance arteries have increased ROS generation, and this increase is linked to NADPH oxidase [16]. Evidence has shown that in SHR and SHRSP rats there was an enhanced production of superoxide (·O 2 ˉ) derived from NADPH oxidase, and this was associated with the upregulation of p22 phox mRNA expression in the aorta [14,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS are naturally produced as a result of oxygen metabolism and include free radicals, like superoxide anion (O 2 .-) and hydroxyl radical ( . OH), and nonradicals, namely H 2 O 2 [6]. The association between oxidative stress and hypertension has been verified in several models of hypertension (reviewed in [6]), such as the SHR, which is a well characterized and extensively used genetic model for studying essential hypertension.…”
Section: Introductionmentioning
confidence: 96%